ANALISIS TREN TOPIK DAN METODOLOGI PENELITIAN SKRIPSI MAHASISWA PENDIDIKAN TEKNOLOGI INFORMASI (PTI) ALUMNI 2022-2025 - Alfian Alfian; Zila Razilu; Hendra Nelva Saputra (STKIP Pesisir Selatan, 2026)
This research analyzes trends in topics and research methodologies in 64 theses by students of the Information Technology Education Study Program (PTI) for academic years 2021/2022–2024/2025, as a basis for program evaluation and development. A descriptive-analytical method was employed, with data collected via documentation studies and analyzed using descriptive statistics (frequency and percentage). Results reveal topics dominated by learning media development (57.8%), followed by information systems (12.5%), networks/infrastructure (7.8%), learning evaluation (7.8%), mobile apps/UI-UX (6.2%), web development (4.7%), and AI/machine learning (3.1%). Methodologically, 37 theses (57.8%) used Research and Development (R&D) with the ADDIE model prevailing, 21 theses (32.8%) applied systems engineering/design, while descriptive quantitative/qualitative methods each covered 2 theses (3.1%). The ADDIE dominance reflects students' inclination toward systematic digital learning product development, while systems engineering indicates pedagogical-technical diversity needing strategic management. Conclusion: the program must formulate policies to diversify topics and methodologies, enhancing research quality and innovation in IT education.